Feral Narratives: The Multispecies Worlds of Max Aub and Andrei Platonov - Gilbert, Erin Morgan (My University, 2024)
In the twentieth century, the definitions and capacities of language, symbolic reasoning, and representation emerged as central preoccupations in studies of modernity, while modernist literature and art brought radical new perspectives and forms into focus for new audiences. At the same time industrialization, urbanization, and compression of time radically transformed both human interactions and more-than-human relationships. In this dissertation, I investigate parallels between the more-than-human imaginaries revealed by the works of Max Aub and Andrei Platonov. Some of their most formally experimental fiction foregrounds the experiences of nonhuman animals and plants, positioning them as active participants in human history. In so doing, they allude to the more-than-human worldmaking practices running through literary history, while drawing on their own experiences and observations to explore multispecies survivance in the Anthropocene. Consequently, their richly intertextual fictions share a critical preoccupation with definitions of the “human” and “nonhuman,” the rhetoric ofanthropomorphism and dehumanization, and the intersection between utopian projects, knowledge production, and anthropogenic change. Their inclusion of plant and animal characters in modernist fiction, I argue, connects ancient more-than-human dialogic storytelling to the formal experimentalism of twentieth century literary practice, and in so doing, Aub and Platonov defamiliarize and ultimately resist hegemonic narrative production.
Thesis (Ph.D.)--University of Washington, 2024
Keywords: cultural studies; dialogism; environmental humanities; Mexican literature; Soviet literature; sympoeisis; Comparative literature; Latin American literature; Slavic literature; To Be Assigned